From Ethnic Nationalisms to Clashing Civilizations: Reconfigurations of (Un)Civil Religion in an Era of Globalization - Busher, Joel (Religion compass, 2012)
One of the main questions currently facing scholars of civil religion is how civil religions, and in particular national civil religions, are being reconfigured in response to the contemporary repositioning of the nation state within the supra-national political, economic, legal and cultural orders entailed by globalization. This article first surveys some of the main arguments to emerge from the civil religion literature in this regard. It then contributes to these debates by outlining how current reconfigurations of national civil religion manifest in the case of a protest movement called the English Defence League (EDL). Specifically, this article describes how rituals and symbols of national belonging have, at least for adherents and supporters of this group, been reinvigorated by infusing them with symbols that invoke notions of civilizational belonging and are replete with references to an imminent "clash of civilizations."